DEAF CHILDREN'S CREATIVITY DEVELOPMENT USING A CULTURAL HABITUATION APPROACH - Latifah Permatasari Fajrin; Mudhofir; Islah (BUANA GENDER : Jurnal Studi Gender dan Anak, 2023)
The present study seeks to foster the development of deaf children's creativity in special kindergartens by employing a cultural habituation approach. The study adopted a qualitative descriptive method that includes observation, interview, and documentation as the data collection method. The reliability of the data used both source and method triangulation. The data analysis techniques involved data reduction, presentation, and conclusion drawing. This study reveals that deaf children's creativity is fostered through lesson preparation, learning implementation, and learning evaluation. The cultural habituation approach to developing the creativity of deaf students involves several integrated components, such as various initiatives to create a culture of inclusion in the school environment to achieve the main objectives of developing creativity, namely instilling self-confidence in children and providing skills to children with disabilities. Keywords: Creativity Development, Deaf Children. Habituation, Culture Â